Pilot scale production and evaluation of mechanical and thermal properties of P(3HB) from Bacillus megaterium cultivated on desugarized sugar beet molasses. Issue 3 (6th August 2021) - Schmid, Maximilian T.; Sykacek, Eva; O'Connor, Kevin; Omann, Markus; Mundigler, Norbert; Neureiter, Markus
Abstract: Production of poly[(R)‐3‐hydroxyalkanoate] (PHA) biopolyesters must become more cost efficient in order to be competitive with conventional plastics as well as other bioplastics. This study introduces a simple and reproducible large‐scale production process of poly(3‐hydroxybutyrate) P(3HB) with Bacillus megaterium based on desugarized sugar beet molasses and compares its material properties with commercially available types of PHA. A repeated batch cultivation system was evaluated in 1.2 L bioreactors and could be maintained for at least six cycles without a decrease in process stability, yielding a concentration of 20.4 g/L cell dry mass and 12 g/L P(3HB) per average process cycle. Feasibility of P(3HB) production was demonstrated at 500 L pilot scale to provide sufficient amounts of product for the determination of mechanical and thermal polymer properties. A volumetric productivity of 0.2 g L −1  h −1 was achieved. The resulting polymer exhibited a high tensile modulus of 3.73 GPa and tensile strength of 38.5 MPa. Despite a lower ductility and Vicat softening temperature, the properties of the recovered P(3HB) are comparable to commercial grade P(HB)HV polymers. Abstract : Poly(3‐hydroxybutyrate), a biobased and biodegradable polymer, can be produced from desugarized sugar beet molasses in batch and repeated batch cultivation with Bacillus megaterium . The feasibility of the process could be demonstrated at 500 L pilot scale. The resulting polymer after extraction was evaluated for its suitability for processing. The mechanical and thermal properties of the polymer proved to be similar to commercially available P(3HB‐3HV), which makes it an interesting candidate for various applications.